Penerapan Analisis Dasar-Dasar Pencegahan Kekerasan Seksual pada Anak di SDN 060919 - Rona Rokania; Malida Putri (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Sexual violence is a social problem that is still common in society and can happen to anyone, both women and men, both children and adults to the elderly. The basic form of prevention of sexual violence against children that can be done is to give them an understanding of the meaning of sexual violence, how to protect themselves and what to do if they experience sexual violence. During this practical field work opportunity, I carried out a mini project in the sexual violence class with NA, who is my client, and 11 grade V students at SDN 060919 and carried out for 3 months from start to finish. Implementation of the mini project through several stages, namely 1) Engagement, Intake, Contract, 2) Assessment, 3) Planning, 4) Intervention, 5) Evaluation and 6) Termination. The results of the implementation of the mini project that has been carried out also show that there has been an increase in NA's understanding such as he understands the concept of sexual violence better and becomes more aware of and knows how to prevent sexual violence from happening to himself, NA becomes wary of strangers and ensures that body parts are private he is not touched by others. This is concrete evidence that the mini project that was implemented succeeded in overcoming NA's problem, namely the lack of self-understanding of sexual violence.